PREDIKSI KAPASITAS PENAMPANG KOLOM BETON BERTULANG DENGAN VARIASI DIAMETER TULANGAN - Samsul A Rahman Sidik Hasibuan; Baskoro Abdi Praja; Iin Irawati (Racic : Rab Construction Research, 2022)
Reinforced concrete column design is the process of determining the dimensions of the columns and reinforcement required with the appropriate quality of concrete and steel so that they can withstand the planned load to work on the column. Unlike the beam design, which was based on the applied load, it is possible to determine the cross-sectional dimensions and reinforcement requirements directly from the design equation, and the column design process is iterative. A column generally experiences axial forces, shear forces, bending moments, and torsional moments. In this paper, cross-sections of reinforced concrete columns are modelled and analyzed using an android application that can be installed via the play store. The application offered by eigenplus named RCC Column Design version 2.1.12 was released on 17 September 2017. The last updated RCC Column Design application was on 25 March 2018. This paper aims to predict the cross-sectional capacity of reinforced concrete columns with variations in reinforcement diameter. The cross-sectional capacity of the column referred to in this paper is the axial capacity, moment capacity, and shear capacity. Furthermore, the value of the cross-sectional capacity of reinforced concrete columns with variations in the diameter of the reinforcement has been obtained. The values ​​obtained are proposed as predictions in this paper.